The protective role of carotenoids in chronic obstructive pulmonary disease: A systematic review and Meta-analysis of observational studies - Jing Sui; Wenbin Shen; Yanni Zhang; Jiarui Liang; Hui Xia; Guiju Sun (Journal of Functional Foods)
Aim of the current study was to clarify the association of carotenoid consumption and chronic obstructive pulmonary disease (COPD) through a meta-analysis of observational studies. We searched the online databases up to August 15, 2024. Both observational studies conducted in human populations were included, and association between level of carotenoids intake/blood and COPD. We performed a meta-analysis using random-effects models. Seven of 9723 records were included in the present study. The odds ratio (OR) between carotenoids consumption and COPD risk was 0.69 (95 % CI: 0.59–0.80, p < 0.001), which indicates a significant protective effect. In addition, subgroup analysis revealed that the various types of carotenoids including a-carotene, β-carotene and cryptoxanthin were significant in COPD (OR = 0.51, 95 % CI: 0.37–0.69; OR = 0.72, 95 % CI: 0.57–0.92; OR = 0.51, 95 % CI: 0.38–0.69, separately). Conclusion: Carotenoids consumption has a protective effect on the risk of COPD.